Role of Mothers’ Nutritional Knowledge, Nutritional Factors on The School Performance - JasminAra Farhana; Farhana Akther; Mesbah Uddin Talukder; Md. Ariful Islam; Md. Torikul Islam; Md. Aminul Haque Bhuyan (Intelektual Pustaka Media Utama, 2015)
A cross sectional study was carried out to investigate the effects of mothers’ nutritional knowledge, health and nutritional factors and socio-economic parameters on school performance among class five students of University Laboratory School, Dhaka. All of the eighty students were selected for this study. This study found there is a strong relationship between mother’s knowledge score and school performance. It was found that mothers’ knowledge score was responsible for 91.1 percent change in school performance. The mean BMI of the mothers was 20.44. We found that the school performance measured by class roll number of the students is significantly related with mothers BMI. There was an imperfect negative association between socio-economic parameters and school performance. But the relationship between the school performances with socio-economic parameters was strongly significant. This study also observed the relationship between Individual Dietary Diversity Score (IDDS) of respondent and marks achieved in class 4 final exam. It is alarming that consumption percentage were low for eggs (30) and milk and milk products (37.5), but majority of the students who consumed milk and milk products (63.3%) and eggs (66.7%) got the highest marks.